Fog and Other Stories - Lowe, Bill; Edited By Chan K. Y. (New York Oxford University Press, 1992)
This series of readers has been completely revised and updated, using a new syllabus and new word structure lists. Readability has been ensured by means of specially designed computer software. Words that are above a level but essential to the story are explained and reinforced within the text.
Include Illustrations and Tables
Keywords: Short stories -- English language -- High interest-low vocabulary books